2014
DOI: 10.1073/pnas.1412768111
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of a self-assembling symmetrical β-propeller protein

Abstract: The modular structure of many protein families, such as β-propeller proteins, strongly implies that duplication played an important role in their evolution, leading to highly symmetrical intermediate forms.Previous attempts to create perfectly symmetrical propeller proteins have failed, however. We have therefore developed a new and rapid computational approach to design such proteins. As a test case, we have created a sixfold symmetrical β-propeller protein and experimentally validated the structure using X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 50 publications
5
118
1
Order By: Relevance
“…The CODV design is thus akin to the design of circularly closed repeat architectures such as b-propeller and b-trefoil folds. 56,[63][64][65] Steric constraints must be matched to permit correct VH/VL pairing of Fv1 and Fv2, as in engineering of circularly closed repeat architectures. Inappropriate linker lengths may result in VH/VL mismatch, leading to dimerization of DVD-Ig type with loss of target affinity as suggested by our initial constructs (Supplements).…”
Section: Discussionmentioning
confidence: 99%
“…The CODV design is thus akin to the design of circularly closed repeat architectures such as b-propeller and b-trefoil folds. 56,[63][64][65] Steric constraints must be matched to permit correct VH/VL pairing of Fv1 and Fv2, as in engineering of circularly closed repeat architectures. Inappropriate linker lengths may result in VH/VL mismatch, leading to dimerization of DVD-Ig type with loss of target affinity as suggested by our initial constructs (Supplements).…”
Section: Discussionmentioning
confidence: 99%
“…These features may be "inherited" through the use of existing sequence information, generating a more naturally funneled energy landscape. Other proteins designed in a similar way, and not yet characterized in detail, may also capture favorable natural features (16)(17)(18). Also, our results show how ligand binding can further smooth the landscape by decreasing the formation of nonnative structure and so promote folding and design success.…”
Section: High Chemical and Protease Resistances Of Threefoil And Othementioning
confidence: 68%
“…Design strategies similar to that used to make ThreeFoil, which use repetition of structural elements designed using existing sequence information and structural modeling with the Rosetta energy function (28), have proven particularly fruitful, with several studies yielding well-folded proteins with high melting points on the first attempt (1,(16)(17)(18). Furthermore, we have shown that ThreeFoil possesses stability, cooperativity and multivalent binding function.…”
Section: High Chemical and Protease Resistances Of Threefoil And Othementioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to elucidate evolutionary models on a selected set of symmetric protein domains such as b-trefoils and b-propellers have been successful [7 ,24]. This inspired the design of symmetric protein structures with a potential for various applications [25][26][27]. Particularly in the last five years, there has been significant progress in identifying protein structural symmetry and describing its relevance to functions and evolution of proteins, which will be the primary focus below.…”
Section: Introductionmentioning
confidence: 99%